Psychometric validation of the Prenatal Distress Questionnaire (PDQ) in pregnant women in Spain. Issue 8 (14th September 2019) - Caparros-Gonzalez, Rafael A.; Perra, Oliver; Alderdice, Fiona; Lynn, Fiona; Lobel, Marci; García-García, Inmaculada; Peralta-Ramírez, María Isabel
ABSTRACT: The Prenatal Distress Questionnaire (PDQ) was developed among English-speaking women in the United States to assess specific worries and concerns during pregnancy. Our aim was to analyze the factor structure of the PDQ, using confirmatory factor analysis, and assess its convergent validity in Spanish women. A sample of 233 pregnant women with ages ranging from 19 to 42 years in the south of Spain (Europe) (January 2015 – March 2016) completed the translated PDQ, the Perceived Stress Scale (PSS) and the Symptom Checklist-90-revised (SCL-90-R). Confirmatory factor analysis revealed a three-factor structure supporting the original PDQ factor structure (χ 2 (31) = 55.43, p = 0.004; CFI = 0.96; RMSEA = 0.058; WRMR = 0.702). The Spanish PDQ significantly correlated with the PSS and SCL-90-R (r's 0.18–0.49, p's < 0.05), providing evidence of convergent validity. These results illustrate that the stress dimensions investigated by the PDQ adequately represent pregnant women's distress across a different cultural context and corroborate the psychometric properties of this instrument previously demonstrated in English-speaking women. The Spanish version of the PDQ can be used by clinical practitioners to evaluate specific worries and concerns women experience during pregnancy.